Criminal Liability for Illegal Issue or Forgery of Documents used to Obtain Superpotent or Poisonous Substances - Mikhail G. Ermakov (Сибирское юридическое обозрение, 2016)
The article deals with the problem of criminal responsibility of individuals for the illegal issue or forgery of documents entitling to obtain superpotent or poisonous substances. The author gives examples from judicial practice, makes recommendations on legislation improvement.